Creating a Harmonious Family Through Social Media Facebook in West Lampung - Muhammad Khusaini; Hariri Hariri; M. Ridho Pratama; Madah Rahmatan (Institut Agama Islam Negeri Palangka Raya, 2022)
Facebook is one of the communication media that is widely used by the community, both urban and rural communities. Facebook not only has a negative impact on its users but also has a positive impact. Social media has a strong positive impact on the family's economy, that the family's needs are met and creating harmonious family relationships compared families that do not use social media as a marketing medium. The study aimed to analyze how to create a harmonious family through social media Facebook in West Lampung Regency. The particular research was empirical legal research. Data collection techniques were observation, interview, and documentation. The study indicated that the use of social media Facebook can create a harmonious family in three families, the subject of the study, in West Lampung Regency. Social media Facebook used to promote the goods that improve the family's economy. This makes the family to be prosperous. In short, it has an impact on the harmony of the family.